Awareness of Metacognitive Strategy in the First Year Engineering College Students – A Study - et.al, R.Gomathy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Reading is one of the most important skills to be focused on to improve the proficiency level in English. Metacognitive reading strategy awareness is the one which helps the L2 learners to regulate their thinking as it creates awareness about the thinking. This also helps the L2 learners to have a plan, intention, proper mental processing that would help them to accomplish cognitive tasks. Furthermore, metacognitive reading strategy awareness skills help to monitor one’s thinking and it also facilitates learning and shows progress in the performance especially for the learners who find it difficult to understand the given text. Among the various strategies, metacognition (Flavell, 1985) (thinking about thinking) and its strategies is one of the processes to make reading a self regulatory learning. But, nowadays, the reading habit among the students has got less priority. This motivates the researchers to identify the awareness level of the L2 learners in reading. And so the L2 learners are tested with the MARSI questionnaire (Kouider Mokhtari and Carla Reichard, 2002). In this regard, general survey has been made among the first year engineering students to learn about their reading strategies. From the survey made, it is understood that they find difficult to make them comfortable and feel monotonous to do a prolonged reading and it is also understood that they are not aware of the reading strategies as they have not been encouraged to do reading from their childhood. And it is also understood that the learners could not enhance their knowledge level as they are not aware of their thinking process. The researchers also made an analysis to find out their awareness about the strategies of Metacognition with the help of the MARSI Questionnaire (Kouider Mokhtari and Carla Reichard, 2002) and to help the learners to know the metacognitive strategies which would act as Scaffolding (Vygotsky, 1978) to develop their autonomous learning to enhance their proficiency in English